Early Retinal Defects in Fmr1−/y Mice: Toward a Critical Role of Visual Dys-Sensitivity in the Fragile X Syndrome Phenotype? - Perche, Olivier; Felgerolle, Chloé; Ardourel, Maryvonne; Bazinet, Audrey; Pâris, Arnaud; Rossignol, Rafaëlle; Meyer-Dilhet, Géraldine; Mausset-Bonnefont, Anne-Laure; Hébert, Betty; Laurenceau, David; Montécot-Dubourg, Céline; Menuet, Arnaud; et al. (Frontiers in Cellular Neuroscience, 2018)
Fragile X Syndrome (FXS) is caused by a deficiency in Fragile X Mental Retardation Protein (FMRP) leading to global sensorial abnormalities, among which visual defects represent a critical part. These visual defects are associated with cerebral neuron immaturity especially in the primary visual cortex. However, we recently demonstrated that retinas of adult Fmr1−/y mice, the FXS murine model, present molecular, cellular and functional alterations. However, no data are currently available on the evolution pattern of such defects. As retinal stimulation through Eye Opening (EO) is a crucial signal for the cerebral visual system maturation, we questioned the precocity of molecular and functional retinal phenotype. To answer this question, we studied the retinal molecular phenotype of Fmr1−/y mice before EO until adult age and the consequences of the retinal loss of Fmrp on retinal function in young and adult mice. We showed that retinal molecular defects are present before EO and remain stable at adult age, leading to electrophysiological impairments without any underlying structural changes. We underlined that loss of Fmrp leads to a wide range of defects in the retina, settled even before EO. Our work demonstrates a critical role of the sensorial dysfunction in the Fmr1−/y mice overall phenotype, and provides evidence that altered peripheral perception is a component of the sensory processing defect in FXS conditions.